2022
DOI: 10.3390/w14050682
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Phosphorus Removal by Calcareous Materials in Long-Term (Two Years) Column Experiment

Abstract: (1) Phosphorus (P) removal has proven difficult in decentralized wastewater treatment systems, and external filters installed with a highly P sorbent material have been proposed to improve the P removal. In particular, calcium (Ca) rich materials have shown promising results. (2) Eight materials (five calcareous materials, one quartz sand, and two Sol–Gel coated calcareous materials) were tested in columns fed with P-spiked tap water for two years. The experiment was operated under four periods with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Expanded clay decreased in removal capacity over the 20‐week duration (from 91 to 42% removal), while RCA maintained consistent removal. Jensen et al (2022) achieved similar (up to 100%) P removal in columns containing a variety of calcareous materials, with P inputs ranging from 3 to 22 mg P/L. Ádám et al (2007) demonstrated above 90% P removal from a 10 mg P/L‐amended secondary wastewater solution within columns containing expanded clay, with average HRTs of around four days.…”
Section: Resultsmentioning
confidence: 98%
“…Expanded clay decreased in removal capacity over the 20‐week duration (from 91 to 42% removal), while RCA maintained consistent removal. Jensen et al (2022) achieved similar (up to 100%) P removal in columns containing a variety of calcareous materials, with P inputs ranging from 3 to 22 mg P/L. Ádám et al (2007) demonstrated above 90% P removal from a 10 mg P/L‐amended secondary wastewater solution within columns containing expanded clay, with average HRTs of around four days.…”
Section: Resultsmentioning
confidence: 98%
“…Fixed-bed column is a technique used to reproduce the adsorption process close to reality, aiming for full-scale applications. This type of system is one of the most effective configurations for treating large volumes of effluents, allowing more efficient use of the adsorbent. , Biochar, electrochemically modified with ferric sludge, iron oxide, calcium alginate, recycled steel byproducts, porous alginate, acrylic amine fiber, hydrated granulated ferric oxide, limestone materials, and concrete powder are among the adsorbents used in fixed-bed column experiments for phosphate removal. However, there are no studies using WC as an adsorbent in fixed-bed columns, reinforcing the novelty of this study regarding phosphate adsorption.…”
Section: Introductionmentioning
confidence: 99%